Control of PV integrated shading devices in buildings: A review. (15th April 2022) - Kirimtat, Ayca; Tasgetiren, M. Fatih; Brida, Peter; Krejcar, Ondrej
Abstract: As a rather new emerging technology, building-integrated photovoltaics (BIPVs) has become easily implementable to the buildings for reducing life-cycle costs and generating energy. One of the major components of the BIPVs is the photovoltaic integrated shading device (PVSDs) that generates electricity by converting the excessive solar radiation into energy to reduce the total energy consumption in the buildings. Being closely related to the zero-energy building concept, the PVSD components should be progressively slanted towards the building and dynamic sun positions in contrast with the fixed panels. Adjustable PVSDs in buildings would play an important role in energy conversion and daylight admission; although this concept is quite new and worth investigating whether the PVSD-control methodology could be the upcoming future of generating electricity while providing natural light. Therefore, for the first time in the literature, a systematic literature review on PVSD designs and advanced control strategies was conducted by surveying the state-of-art articles. Summarizing the current body of knowledge, the existing studies were collected between 2012 and 2021 in a literature matrix consisting of the mutual aspects like PVSD and building types, methods, climates and energy saving ratio. Given the provided overview and very detailed summary of the PVSD designs and related control strategies, this review would be a valuable guide for future studies.